Analisis Dampak Penggunaan Media Pembelajaran terhadap Karakter Profil Pelajar Pancasila Kepada Siswa Kelas V SDK Manumuti (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
This study aims to analyze the impact of using learning media on the character development of Pancasila students in grade V of Manumuti Elementary School. This study used a qualitative approach with a case study. Data collection was conducted through observations that measured students' perceptions of the learning media and based on Pancasila student profile indicators. The qualitative approach allows researchers to gain a deeper understanding of the phenomenon being studied by examining in detail different cases within the problem being studied. Information was collected directly from the field through verbal expressions and observation of actions. The results of the study indicate that the implementation of learning media in grade V of Manumuti Elementary School varied and presented. Meanwhile, the character profile of Pancasila students in grade V showed positive development in the dimensions of mutual cooperation, independence, faith, devotion to God Almighty, and noble character. This study concludes that the use of planned and relevant learning media is an effective strategy in strengthening the character profile of Pancasila students.